Environmental damage cost and exergoenvironmental evaluations of piston prop aviation engines for the landing and take-off flight phases. (15th December 2022) - Balli, Ozgur; Kale, Utku; Rohács, Dániel; Hikmet Karakoc, T.
Abstract: This study presents a comprehensive investigation of the environmental damage cost, exergoenvironmental and life cycle assessment (LCA) analyses of four piston prop aviation engines (AE) entitled as AE1, AE2, AE3, and AE4 for different flight conditions. The data of energetic, exergetic, economic, and exergoeconomic as well as emission are firstly given as a briefly. Then, cost formation of environmental damages, LCA, and exergoenvironmental analyses are realized. AE3 has minimum specific environmental damage with 0.0380 /MJ and the lowest specific exergoenvironmental cost with 0.360 /MJ for take-off phase. Besides, minimum environmental impact values of engine shaft power are estimated to be 29.33 mPts/MJ for AE1 in taxi phase, 23.93 mPts/MJ for AE3 in take-off phase, 26.36 mPts/MJ for AE1 in climb-out phase, and 25.20 mPts/MJ for AE2 in approach phase. Fuel consumption is main contributor for environmental impact with over 89%. The highest relative environmental differences is occurred in AE4 by 1001.69% for taxi phase while AE1 has minimum exergoenvironmental factor. and AE3 has minimum values of environment impact point costs. As a result, AE3 is the best engine in the perspective of thermodynamically, economically and environmentally. Highlights: Environmental damage cost, exergoenvironmental and life cycle assessment analyses are done for piston prop aviation engines. Investigation is realized for four different engine and landing and take-off flight (LTO) phases. Fuel consumption is main contributor for environmental impact rate. AE3 is the best engine in the perspective of thermodynamically, economically and environmentally.